A simulation study of sensor behavior for non-invasive electrical resistance tomography - Yasmin, Abdul Wahab; Nur Faten Faseha, Hisham; Maziyah, Mat Noh; Zainah, Md. Zain; Normaniha, Abd Ghani; Mohd Anwar, Zawawi; M. S., Najib; Ruzairi, Abdul Rahim (Malaysian Society for Computed Tomography and Imaging (MyCT), 2020)
The non-invasive method is one of the common methods applied in process plants, compared to other sensing methods. The paper aims to investigate the feasibility study of sensor behaviour implemented in non-invasive Electrical Resistance Tomography (ERT) by applying various materials and shapes for electrodes. Based on a quasi-static electric field, a 3D simulation using finite element model software (COMSOL Multiphysics) was applied to investigate and analyse the sensor behaviour. A 100 mm outer diameter and 2 mm thick acrylic pipe was used for the non-invasive ERT system. A studying of a fringe effect also was the focus in this project. Thus, it is believed that the implementation material such as copper and steel, circle shape and the fringe effect of the electrode could allow the electricity to be emitted and detect significantly. The non-invasive of ERT system would also gave an alternative way for industry to monitor the performance of the process plants.